Breaking the triple lock: further education and transformative teaching and learning. Issue 6 (21st June 2018) - Duckworth, Vicky; Smith, Rob
Abstract : Purpose: The purpose of this paper is to explore data from the University and College Union (UCU) Further Education in England: Transforming Lives and Communities research project and through this the paper develops a distinctive, theorised conceptualisation of transformative teaching and learning (TTL). Design/methodology/approach: The research used an approach grounded in critical pedagogy utilising digital methods, including video interviews, to collect narratives from learners, teachers, family members and their communities from colleges across Britain. Findings: Within a context in which there are structural pressures militating in favour of instrumentalising students in further education, TTL offers a way of theorising it as a transformative critical space that restores students' hope and agency. The research provides evidence of how further education offers this "differential space" (Lefebvre, 1991 ) and subverts the prescriptive, linear spaces of compulsory education. While productivist approaches to vocational education and training support ideologies that legitimate prescribed knowledge, reproducing inequality and injustice through the practices employed (Ade-Ojo and Duckworth, 2017; Duckworth and Smith, 2017b ), TTL shifts to a more holistic approach, achieving a different level of engagement with students. Practical implications: The findings suggest that the TTL lens is a way of focusing on the dignity, needs and agency of further education students. The lens allows us also to identify how the existing structures associated with funding and marketisation can undermine the potential of TTL to activate students' agency through education. Originality/value: Extending on existing literature around transformative learning, and drawing on a range of theoretical frameworks, the paper formulates a new, contextually specific conceptualisation of TTL.